2018
DOI: 10.1111/nmo.13487
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose linaclotide is effective and safe in patients with chronic constipation: A phase III randomized, double‐blind, placebo‐controlled study with a long‐term open‐label extension study in Japan

Abstract: Background A previous phase II dose‐ranging study of linaclotide in a Japanese chronic constipation (CC) population showed that 0.5 mg was the most effective dose. This study aimed to verify the hypothesis that 0.5 mg of linaclotide is effective and safe in Japanese CC patients. Methods This was a Japanese phase III randomized, double‐blind, placebo‐controlled (part 1), and long‐term, open‐label extension (part 2) study of linaclotide. CC patients (n = 186) diagnosed using the Rome III criteria were randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 29 publications
2
28
0
2
Order By: Relevance
“…For the sensitivity analysis involving trials on CC only, there was no significant difference in the efficacy of linaclotide 500 μg and linaclotide 600 μg. This is consistent with the findings from previous dose-determining studies in Japanese patients in which similar efficacy was observed between different linaclotide doses for patients with CC [31,32]. The reason for the similar efficacy between linaclotide 500 and 600 μg that was observed in CC trials only may be attributed to a difference in linaclotide reactivity in CC and IBS-C patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For the sensitivity analysis involving trials on CC only, there was no significant difference in the efficacy of linaclotide 500 μg and linaclotide 600 μg. This is consistent with the findings from previous dose-determining studies in Japanese patients in which similar efficacy was observed between different linaclotide doses for patients with CC [31,32]. The reason for the similar efficacy between linaclotide 500 and 600 μg that was observed in CC trials only may be attributed to a difference in linaclotide reactivity in CC and IBS-C patients.…”
Section: Discussionsupporting
confidence: 91%
“…1). Manual searching identified 4 trials (phase 2 and 3 results of linaclotide in Japan, ClinicalTrials.gov identifiers: NCT01714843, NCT02316899, NCT02425722, and NCT02809105) that were accepted for publication at the time of this study and have since been published [30][31][32][33]. After removal of duplicates, trials were excluded if they were not aimed at studying the treatment effects of CC, had interventions not included in the pre-determined 43 oral drug list, did not report change in SBM before and after treatment as the endpoint, included patients below the age of 18 years, were evaluating organic constipation, or were non-randomized trials or pre-clinical studies.…”
Section: Study Inclusionmentioning
confidence: 99%
“…Linaclotide was approved in North America for treating CC with doses of 0.145 mg per day [10] and 0.072 mg per day [7]. A phase III RCT in Japan confirmed 0.5 mg per day [18] to be the optimal dose for patients suffering from CC, which is consistent with the results of this study. High doses of linaclotide significantly improved the symptoms of CC patients compared to the placebo.…”
Section: Discussionsupporting
confidence: 88%
“…Admittedly, the oral dose of linaclotide that exerts beneficial effects in terms of weight loss of obese rodents is higher than the recommended doses indicated for irritable bowel syndrome and chronic idiopathic constipation. However, clinical studies using high doses of linaclotide reported its efficacy and safety in patients with chronic constipation [27] and colorectal cancer prevention [28]. It is also important to note that preclinical studies administering linaclotide at higher doses (10 mg/kg) than in the present work showed that the parent drug was completely degraded to its metabolite within 30 min [29].…”
Section: Discussionmentioning
confidence: 83%